Frequency and risk factors for cognitive dysfunction in peritoneal dialysis patients. Issue 12 (13th October 2022) - Gamage, Isuru; Dhar, Arup; Tregaskis, Peter; Wilson, Scott
Abstract: Objective: There is limited data on cognition in patients undergoing peritoneal dialysis (PD). We assessed prevalence and associated risk factors of neurocognitive impairment (NCI) in PD patients. Design and Methods: A cross‐sectional cohort study of 149 PD patients at a single centre between 2016 and 2020 who underwent neurocognitive screening at defined intervals by Addenbrooke's Cognitive Examination – Revised (ACE‐R) with incorporated Mini‐Mental State Examination (MMSE). Paired‐sample t ‐test was used to compare cognitive performance to the general population and compare cohorts for dichotomous risk factors. Residual renal function (RRF) and clearance kinetics were evaluated using local regression models. Sub‐analysis was performed in patients with cerebrovascular disease (CVD). Results: Patients on PD performed poorly in ACE‐R screening compared to population norms, with discrepancy in all cognitive domains. In patients without CVD, attention and language domains were comparable to norms. The MMSE detected cognitive impairment in 2% of studied patients, significantly fewer than when the ACE‐R was applied (32%). Age, gender, diabetic status and depression were associated with lower neurocognitive screening performance ( p < .05). Dialysis vintage beyond 12 months conferred poorer cognitive performance. RRF correlated with cognitive performance. Conclusion: Patients on PD have higher prevalence of NCI than the general population, primarily with impairments in memory, fluency and visuospatial reasoning. CVD confers poorer performance in attention and language domains. The MMSE is ineffective in detecting subtle NCI in this population compared with ACE‐R. Risk factors for NCI include age, gender, diabetic status, depression and vintage beyond 12 months. Protective factors include RRF. Summary at a glance: This cross‐sectional cohort study found that patients on peritoneal dialysis performed poorer than the general population on detailed neurocognitive screening, with strongest impairment in memory, fluency and visuospatial reasoning. Depression, age, gender, diabetic status and dialysis vintage beyond 12 months were the strongest risk factors for cognitive impairment. Residual urine output correlated with better cognitive performance.